Factors influencing brain natriuretic peptide levels in healthy pregnant women. (1st February 2017) - Mayama, Michinori; Yoshihara, Masato; Uno, Kaname; Tano, Sho; Takeda, Takehiko; Ukai, Mayu; Kishigami, Yasuyuki; Oguchi, Hidenori
Abstract: Background: The normal range of plasma brain natriuretic peptide (BNP) in pregnant women is still unclear. Moreover, pregnant women experience dynamic body weight changes and suffer from anemia, but effects on maternal BNP have not been investigated. This study aimed to reveal the normal plasma BNP range and examine the effects of physiological changes on BNP among pregnant women. Methods and results: Plasma BNP, hemoglobin, plasma creatinine and BMI were measured in 58 non-pregnant control women and in 773 normal pregnant women at late pregnancy, early postpartum and 1-month postpartum. Mean plasma BNP (in pg/mL) was 11.8 (95% confidence interval: 0–27.5) in non-pregnant women, 17.9 (0–44.7, p < 0.001) at late pregnancy, 42.5 (0–112.6, p < 0.001) early postpartum and 16.1 (0–43.9, p = 0.001) 1-month postpartum. Multiple regression analysis revealed that pre-delivery BNP levels were negatively correlated with BMI (p < 0.001) and hemoglobin (p = 0.002) and positively correlated with creatinine (p < 0.001). Post-delivery BNP was positively associated with body weight change during pregnancy (p = 0.001) and post-delivery creatinine (p = 0.010) but negatively associated with body weight loss at delivery (p < 0.001) and post-delivery hemoglobin (p = 0.004). Conclusion: Even normal pregnancy affects plasma BNP, particularly in the early postpartum period, indicative of cardiac stress. Plasma BNP levels are affected by BMI, body weight changes, creatinine and hemoglobin levels; therefore, these factors should be considered when analysing cardiac function and the physiological implications of BNP levels in pregnant women.